2021
DOI: 10.3390/vaccines9091029
|View full text |Cite
|
Sign up to set email alerts
|

“Vaccinate, Do Not Hesitate!”. Vaccination Readiness against COVID-19 among Polish Nursing Undergraduate Students: A National Cross-Sectional Survey

Abstract: COVID-19 vaccination raises numerous concerns among the public, and also among medical personnel including nurses. As nurses play a crucial role in the process of vaccination, it is important to recognize the attitudes of students of nursing, nurses in spe, toward COVID-19 vaccination, as well as to define the factors influencing students’ pro-vaccine choices. The study was conducted between March and April 2021 at all medical universities in Poland educating nurses in spe. The study included 793 first-degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…To the best of our knowledge, the research results presented in this paper are the first to describe anxiety levels among nursing students after more than a year since the onset of the COVID-19 pandemic, at a time when it is possible to receive the COVID-19 vaccine, and when most medical students in Poland were already vaccinated [40].…”
Section: Resultsmentioning
confidence: 95%
“…To the best of our knowledge, the research results presented in this paper are the first to describe anxiety levels among nursing students after more than a year since the onset of the COVID-19 pandemic, at a time when it is possible to receive the COVID-19 vaccine, and when most medical students in Poland were already vaccinated [40].…”
Section: Resultsmentioning
confidence: 95%
“…The most important reason for the refusal of a COVID-19 vaccine was doubts about the safety, efficacy, and effectiveness of the vaccine (72.4%) [ 65 ]. In Poland, most nursing students (77.2%) were vaccinated against COVID-19 [ 66 ]. Every other person in the non-vaccinated group declared his or her intention to get a vaccination.…”
Section: Health and Vaccine Literacymentioning
confidence: 99%
“…Every other person in the non-vaccinated group declared his or her intention to get a vaccination. Importantly, easy access to vaccines is the most critical factor impacting Polish nursing students’ positive attitudes toward COVID-19 vaccination [ 66 ].…”
Section: Health and Vaccine Literacymentioning
confidence: 99%
“…Moreover, the analysis of Facebook users' comments posted on the selected Polish media profiles in November and December 2020 indicated that 85% of content related to the COVID-19 vaccines was negative with numerous conspiracy theories such as that the vaccines were created only for the profit of pharmaceutical companies or that the vaccines were already prepared before the pandemic [58]. This may also explain, at least partially, the high level of vaccine hesitancy seen in the Polish population right before and after the authorization of the first COVID-19 vaccines [59,60]. The first polls, conducted in November 2020, demonstrated that only 20% of Poles declared a willingness to vaccinate, a figure that increased to 36% in December 2020 and to 55% in mid-February 2021 [61,62].…”
Section: Discussionmentioning
confidence: 99%